Reversible Watermarking Based on Sorting Prediction Algorithm - Khalid, Edris (Penerbit UMP, 2015)
Reversible watermarking has drawn a lot of interest in recent years. Sachnev et al proposed reversible watermarking algorithm by combining prediction technology, histogram shifting technology and sorting technology, which has good performance.However, their method is against the characteristics of the human visual system. In this paper, we propose a reversible watermarking algorithm to improve Sachnev et al algorithm by using new sorting method. The performance of the proposed reversible watermarking algorithm is evaluated and compared with Sachnev et al method and other methods. The results indicate that the proposed algorithmhas good performance than Sachnev et al method and can embed data with less distortion.